A content analysis of research on technology use for teaching mathematics to students with disabilities: word networks and topic modeling - Mikyung Shin; Min Wook Ok; Sam Choo; Gahangir Hossain; Diane P. Bryant; Eunyoung Kang (SpringerOpen, 2023)
Abstract The purpose of this study was to conduct a content analysis of research on technology use for teaching mathematics to students with disabilities. We applied word networks and structural topic modeling of 488 studies published from 1980 to 2021. Results showed that the words "computer" and "computer-assisted instruction" had the highest degree of centrality in the 1980s and 1990s, and "learning disability" was another central word in the 2000s and 2010s. The associated word probability for 15 topics also represented technology use within different instructional practices, tools, and students with either high- or low-incidence disabilities. A piecewise linear regression with knots in 1990, 2000, and 2010 demonstrated decreasing trends for the topics of computer-assisted instruction, software, mathematics achievement, calculators, and testing. Despite some fluctuations in the prevalence in the 1980s, the support for visual materials, learning disabilities, robotics, self-monitoring tools, and word problem-solving instruction topics showed increasing trends, particularly after 1990. Some research topics, including apps and auditory support, have gradually increased in topic proportions since 1980. Topics including fraction instruction, visual-based technology, and instructional sequence have shown increasing prevalence since 2010; this increase was statistically significant for the instructional sequence topic over the past decade.